Response of Verticillium fungicola var. fungicola, Mycogone perniciosa_and Cladobotrym sp. Mushroom Pathogens to Some Essential Oils - Brankica Tanović (Pesticidi i Fitomedicina, 2006)
Antifungal activity of 18 essential oils was evaluated against Verticillium fungicola var. fungicola, Mycogone perniciosa and Cladobotryum sp., the causal agents of button mushroom diseases. Essential oils including: turpentine, basil, lemon, mint, fenchel, rose geranium, anise, cinnamon, scots pine, clove, thyme, juniper, lavender, orange, eucalyptus, rosemary, bergamot orange and tea tree, were screened for their effectiveness against the pathogens in vitro. In order to investigate fungicidal activity, isolates were exposed to the volatile phase of the oils for seven days. Of the 18 essential oils analyzed, cinnamon, clove, thyme, and tea tree showed the highest antifungal activity against all investigated mycopathogens,with Minimum Fungicidal Concentration (MFC) being 0.02 μl/ml of air. Turpentine essential oil expressed the lowest antifungal effect to all isolates tested.